2021
DOI: 10.21203/rs.3.rs-180966/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Citywide serosurveillance of the initial SARS-CoV-2 outbreak in San Francisco

Abstract: Serosurveillance provides a unique opportunity to quantify the proportion of the population that has been exposed to pathogens. Here, we developed and piloted Serosurveillance for Continuous, ActionabLe Epidemiologic Intelligence of Transmission (SCALE-IT), a platform through which we systematically tested remnant samples from routine blood draws in two major hospital networks in San Francisco for SARS-CoV-2 antibodies during the early months of the pandemic. Importantly, SCALE-IT allows for algorithmic sample… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…Results from this study indicated large disparities in burden of infection among Californians, particularly among Hispanic/Latinx persons compared with non-Hispanic/Latinx White persons. These data support other findings in California, which have documented seroprevalence up to 3 times as high among Hispanic/Latinx persons compared with non-Hispanic/Latinx White persons [ 6 , 22 , 23 ]. We also reported differences in seroprevalence by insurance status and workplace.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Results from this study indicated large disparities in burden of infection among Californians, particularly among Hispanic/Latinx persons compared with non-Hispanic/Latinx White persons. These data support other findings in California, which have documented seroprevalence up to 3 times as high among Hispanic/Latinx persons compared with non-Hispanic/Latinx White persons [ 6 , 22 , 23 ]. We also reported differences in seroprevalence by insurance status and workplace.…”
Section: Discussionsupporting
confidence: 91%
“…The estimated IFR was 0.8% for adults, and we found that only 1 in 3 SARS-CoV-2 infections in adults was reported to the CDPH through early November 2020. Disparities documented in our study by ethnicity and insurance status may be larger than previously suggested by local seroprevalence studies [ 6 , 23 ] and surveillance data [ 28 ]. Taken together, these data underscore the continued need to focus public health interventions, including access to testing and vaccination in socioeconomically vulnerable communities, which are the most heavily impacted.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…To measure disparities in both infection rates and vaccination, we leveraged a SARS-CoV-2 serosurveillance platform launched in March 2020 that utilizes residual blood samples taken from two hospital networks in San Francisco. Estimates derived from this platform during the first wave of the pandemic showed seroprevalence in Latinx individuals to be nearly two times higher than in white individuals, and nearly two times higher in homeless individuals than the population average (9). We collected samples from 1,014 individuals undergoing routine blood draws between February 4 and February 17, 2021, capturing transmission during the first 11 months of the epidemic and the early roll-out of vaccination.…”
Section: San Francisco As a Case Studymentioning
confidence: 99%
“…At the time of testing, dried blood from the Mitra device was eluted overnight at 4 °C, based on published protocols [24]. The eluate was diluted with 2% non-fat dry milk to1:80 and utilized for detection of IgG antibodies to recombinant receptor binding domain (RBD) of the SARS-CoV-2 Spike (100 ng/well), utilizing standard enzyme-linked immunosorbent assay (ELISA) protocols [25,26]. To interpret the ELISA data, we calculated a cut off of OD 405 = 0.3 (mean + 3 standard deviations) by testing finger-stick eluates from 50 COVID-19 PCR-negative subjects.…”
Section: Methodsmentioning
confidence: 99%